Cystic intrathoracic derivatives of the foregut and their complications. Issue 4 (July 1973) - Kirwan, W. O.; Walbaum, P. R.; McCormack, R. J. M.
Abstract : It is suggested that these lesions should be classified into three main categories based on embryology—bronchogenic cyst (resulting from a defect of lung budding), intramural oesophageal cyst (true duplication), and enteric cyst (resulting from the split notochord syndrome). A series of 41 patients is reported. Seven of our patients suffered complications, and in two cases these nearly resulted in the death of the patient. These complications are described and their serious import is used to emphasize the desirability of surgical removal of all these foregut derivatives before complications ensue.